Conditions of Coral Reef and Target fish in Waters of Maitara Islands - Mohdi Umanahu; Umar Tangke; Syahnul Sardi Titaheluw (Musamus Fisheries and Marine Journal, 2020)
This research was carried out with a survey method during August 2019 with the aim of knowing the biodiversity of target fish and their potential in the coral reef ecosystem in the waters of Maitara Island, North Maluku Province by collecting primary and secondary data in the form of coral reef conditions (lifeform), fish conditions (diversity, uniformity and dominance) as well as environmental parameter data in the form of temperature, salinity, current velocity, and brightness. The collection of data on the condition of coral reefs and fish was carried out simultaneously, namely 1 dive at each station. Visual census method is used for reef fish data. The results of visual observation of reef fish in the waters of Maitara Island found that there were 13 familyes included in the major fish group consisting of 7 familyes, 1 family of indicator fish and 5 target fish groups. The reef fish found at the observation location of station 1 consisted of 59.3% major fish groups, 24.2% target fish and 16.5% indicator fish and at station 2 reef fish consisted of 62.1 major fish groups. %, target fish is 23.8% and indicator fish is 4.1%. Overall, the results of the visual observations of reef fish showed that major fish were the most dominant, found as much as 66.7% of the target fish groups were 23.9% and indicator fish groups were 9.4%. The lack of presence of indicator fish groups shows that the fertility of the coral reef ecosystem in the waters of Maitara Island is no longer in good condition, because the indicator fish group is a type of fish that indicates good and bad parameters of coral reef conditions in the waters.